Injuries and disorders among young ice skaters: relationship with generalized joint laxity and tightness - Okamura S; Wada N; Tazawa M; Sohmiya M; Ibe Y; Shimizu T; Usuda S; Shirakura K (Dove Medical Press, 2014)
Shinobu Okamura,1 Naoki Wada,1 Masayuki Tazawa,1 Makoto Sohmiya,1 Yoko Ibe,1 Toru Shimizu,1 Shigeru Usuda,2 Kenji Shirakura1 1Department of Rehabilitation Medicine, Gunma University Graduate School of Medicine, Maebashi, Gunma, Japan; 2Department of Physical Therapy, Gunma University School of Health Science, Maebashi, Gunma, Japan Abstract: This study retrospectively investigated 192 teenage speed and figure skaters with prior injuries documented by an athletes’ questionnaire, who underwent a physical examination to assess their muscle tightness and generalized joint laxity. In all athletes, the degree of muscle tightness and joint laxity were measured by a standardized physical examination. A descriptive report of the types of injuries showed a predominance of fractures, ligament injuries, enthesitis, and lower back pain. Approximately 5% of all skaters tested positive for tightness, while 25.8% of figure skaters and 15.2% of speed skaters had generalized ligamentous laxity. Statistical testing showed an association between ankle sprains and muscle tightness, and an association between knee enthesitis and muscle tightness in skating athletes. There was also an association between lower back pain and generalized joint laxity, which held true only for the male skaters. Keywords: sports injury, skating, junior athlete, tightness, joint laxity, medical checkup